2011
DOI: 10.1387/ijdb.103249kp
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish enhancer trap line recapitulates embryonic aquaporin 1a expression pattern in vascular endothelial cells

Abstract: Aquaporin 1 (Aqp1) is a water channel protein, expressed widely in microvascular endothelial cells and implicated in mammalian tumor angiogenesis. However, its developmental expression has not yet been characterized in great detail. An enhancer trap screen was performed using a Tol2-derived GFP reporter in zebrafish embryos. An insertional Et(GBT-B1)tpl1 line was identified that has reporter insertion in the vicinity of the aqp1a gene. We further characterized the embryonic expression pattern of this GFP repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Recently, it was demonstrated that AQP1a1 is expressed on the skin of yolk sac in larval zebrafish [16], [17], and expression of zebrafish AQP1a1 in Xenopus oocytes was associated with an increase in water influx [7]. Here we show that in larval zebrafish, AQP1a1 is expressed predominantly on the basolateral membrane of ionocytes on the yolk sac epithelium.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Recently, it was demonstrated that AQP1a1 is expressed on the skin of yolk sac in larval zebrafish [16], [17], and expression of zebrafish AQP1a1 in Xenopus oocytes was associated with an increase in water influx [7]. Here we show that in larval zebrafish, AQP1a1 is expressed predominantly on the basolateral membrane of ionocytes on the yolk sac epithelium.…”
Section: Discussionsupporting
confidence: 48%
“…In larval zebrafish, the results of in situ hybridization demonstrated that AQP1a is expressed on the skin of the yolk sac, presumably to regulate water influx [16], [17]. However, it is still unclear whether AQP1 has any physiological role in facilitating transcellular water movement in teleost fish in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…A gene-trap fli1b tpl50Gt mutant line was generated in a Tol2 -mediated insertional mutagenesis screen using GBT-B4 gene trap vector (C. Seiler et al, unpublished data, 2015) similar to the recently published GBT-B1. 42-44 The gene trap transposon (Figure IIE in the online-only Data Supplement) integrated into the first intron and near the start of the coding sequence resulting in a Gal4-VP16 fusion protein lacking the ETS DNA-binding domain (Figure IIF through IIH in the online-only Data Supplement); therefore, the mutation is expected to be null or severe hypomorph. 43 Consistent with this view, the gene-trap disruption resulted in an 18.5-fold (5.4±2.0%) reduction in full-length fli1b message as determined by reverse transcription polymerase chain reaction and whole-mount in situ hybridization (Figure IIM, IIN, and IIP in the online-only Data Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…The abundance of gas-permeable membrane channels is the second key regulator of membrane permeability to CO 2 (Itel et al, 2012). In larval zebrafish, AQP1a1 is expressed in several membranes of potential relevance to CO 2 excretion, including endothelial cells of the arterial vasculature (Rehn et al, 2011), RBCs ( present study; Chen et al, 2010) and ionocytes of the yolk sac epithelium (Chen et al, 2010;Kwong et al, 2013). Loss of RBCs, and hence RBC AQP1a1, by treating the developing zebrafish with phenylhydrazine had no significant impact on CO 2 excretion, and AQP1a1 Values were normalized relative to 18S (for mRNA) or β-actin (for protein), and values for HEA-exposed larvae then were expressed relative to those of the corresponding control group.…”
Section: Discussionmentioning
confidence: 99%